Educating young children with autism spectrum disorders - Barton, Erin Elizabeth; Harn, Beth.; Sage eBooks (Thousand Oaks, Calif. : Corwin, 2012)
This guide for practitioners - early interventionists, teachers, school counsellors and psychologists - provides practical strategies for addressing the unique needs of children on the autism spectrum and their families. Drawing on current research and evidence-based practice, the authors discuss the causes of autism and present methods for educating children and assisting their families in supporting the educational process. Each chapter focuses on a critical issue and offers solutions.
A joint publication with the National Association of School Psychologists.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Autistic children -- Education (Early childhood); Electronic books